Scientific Writing Series: Cross-Sectional studies - Quispe, Antonio M. (2020)
Cross-sectional studies are characterized by the simultaneous measurement of exposure and the outcome of interest. They are the ideal design to estimate prevalence, analyze the diagnostic accuracy of a test and validate instruments, for which it is essential to control information bias, selection, and confusion either by design or by analysis. It is also crucial to choose the appropriate association measure for each outcome of interest, call the odds ratio for rare events, and the prevalence ratio for frequent events. Finally, for its writing and publication, it is recommended to review the STROBE and STARD guidelines.